PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA PEMASARAN DENGAN PENGELOLAAN MODAL KERJA SEBAGAI VARIABEL MEDIASI PADA UMKM DI KOTA BONTANG - Yuliati Yuliati; Alifia Dilla Sastaviyana; Jemsi Silaban; Rahmawati (JIM : Journal Of International Management, 2026)
This study aims to analyze the effect of Human Resource (HR) Competence on Marketing Performance with Working Capital Management as a mediating variable in Small and Medium Enterprises (SMEs) in Bontang City, East Kalimantan. The study employed a quantitative approach using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with SmartPLS software. Data were collected from 75 respondents using purposive sampling technique. The research instrument consisted of 13 valid indicators after the elimination process. The analysis results show that: (1) HR Competence does not directly and significantly influence Marketing Performance (path coefficient = 0.103; T-statistic = 1.022; p = 0.307); (2) HR Competence positively and significantly influences Working Capital Management (path coefficient = 0.598; T-statistic = 8.390; p = 0.000); (3) Working Capital Management positively and significantly influences Marketing Performance (path coefficient = 0.624; T-statistic = 8.095; p = 0.000); and (4) HR Competence positively and significantly influences Marketing Performance through Working Capital Management as full mediation (indirect coefficient = 0.373; T-statistic = 5.830; p = 0.000). The R-Square value for Marketing Performance is 0.477 and for Working Capital Management is 0.358. This study confirms that Working Capital Management fully mediates the relationship between HR Competence and Marketing Performance in Bontang City SMEs.